PRODUCTIVITY MEASUREMENT MODEL AT PT PANGAN BAROKAH ABADI USING THE GREEN PRODUCTIVITY APPROACH AND GREEN VALUE STREAM MAPPING (Jurnal Teknologi Industri Pertanian, 2026)
This study aims to develop a productivity measurement model at PT Pangan Barokah Abadi using the Green Productivity approach and Green Value Stream Mapping (GVSM). The company is a Small and Medium Enterprise (SME) producing traditional snacks in the form of Javanese rambak crackers (kerupuk rambak Jawa) and faces major challenges, including high energy consumption, emissions, and waste generation throughout its production processes. Therefore, a productivity improvement strategy that simultaneously emphasizes economic efficiency and environmental performance is required. GVSM was applied to map value streams, resource consumption, and waste generation from five primary environmental sources: energy, water, solid waste, transportation, and emissions. Furthermore, the Analytical Hierarchy Process (AHP) method was employed to determine green productivity criteria and indicators and to calculate their priority weights in a structured and systematic manner. The results produced a productivity measurement model consisting of three main components: the Economic Productivity Index (EPI), the Environmental Productivity Index (EnPI), and the Green Productivity Index (GPI) as an integration of both dimensions. This model provides a quantitative assessment of economic efficiency and environmental performance and serves as a strategic decision-support tool for achieving operational sustainability in SMEs.Keywords: analytical hierarchy process, green productivity, green value stream mapping, SMEs, Rambak Crackers